Implementación de un módulo de entrenamiento para la asignatura de Electrónica de la carrera de Electromecánica en la Universidad Técnica de Cotopaxi Extensión La Maná. - Proaño Tixilema, Raúl Stalin (2023)
This research project aims to implement a training module for the subject of electronics that will be a tool for teaching electronic circuits that will be carried out in the electromechanics laboratory belonging to the Technical University of Cotopaxi La Maná Extension, this module It develops a function of vital relevance for student performance. In the research process, it started from the syllabus of the subject of electronics where theoretical classes are taught on the behavior of diodes, transistors, operational amplifiers, these components are used to build all types of electronic circuits. The module will allow students to practice connecting electronic circuits, which is why the module has several components in order to meet the need when designing a circuit and putting it into practice. The project proposal is an electronic circuits module, which will allow students to obtain greater interest in the advances of electronics, increasing the growth of new projects such as the execution of electronic circuits that will help their knowledge as electromechanical engineers. The module meets the need for the main components for a practical execution and the guides help students to make connections in correct ways with the physical operation, which is why the Oscilloscope measurement tool is essential to see the behavior of the various circuits that are made in the electronic module